Evaluation of Finite Element Modeling Methodology for Composite Materials - Chakravarthy, CH Nithin (International Journal of Psychosocial Rehabilitation, 2020)
Over past few decades, tremendous innovations have occurred in the aerospace/marine industry because of environmental regulations, rising fuel costs, increase in airline traffic etc. These reasons lead to more usage of composite materials in the primary structural components. These materials are known for their high strength and stiffness to weight ratio and hence used in structural applications where there are stringent weight requirements as in aerospace and marine applications.Because of recent advancements in manufacturing techniques, there is increase in trend of using composite materials in many complex aerospace and marine structures. Since design and analysis of these structures becomes extremely difficult, Finite Element method is used extensively in most of the applications to reduce time and effort.Marine propellers are generally doubly curved and tapered with solid cross sections due to acoustic requirements and hence modelling of these kind of propeller blades becomes extremely difficult in Finite Element Method. In this thesis, different FE modelling strategies for a complex shaped 3D composite structure is discussed and compared. By selecting a more appropriate methodology, a typical marine propeller blade is analysed and results are compared with metal blade.